Interdisciplinary approach to the treatment and management of dyslipidemia in Albania - Pasho, Ina; Dibra, Marinela; Pasho, Erjona; Goda, Era; Burreli, Jurgen; Troja, Erjon (International Journal of Scientific Research and Management (IJSRM), 2024)
The prevalence of dyslipidemia in Albania is approximately 60%. Since the total adult population is 2.173 million, there are about 1.3 million patients with dyslipidemia.We conducted a descriptive study, through the distribution of questionnaires and interviews of outpatient doctors, laboratory doctors and pharmacists, as some of the most important components of this journey. 100 professionals for each specialty were included in the study.The medical specialists included in the study during their daily practice are involved in situations of management, treatment and follow-up of patients with dyslipidemia, in a significant percentage; doctors 90-100% and pharmacists with over 70%. Based on the therapeutic alternatives present in our country, it turns out that statins are the most commonly used therapy, and the treatment starts with low doses and in most cases the maximum dosage is not reached, as a result of the side effects that this therapy causes. These professionals are also involved in the long-term follow-up of patients, where in over 80% of cases they suggest returning for consultations every three months, or they do the evaluation of the cardiovascular risk factors for this category of patients, in over 50% of cases.The role of all medical specialties involved in the management of dyslipidemias consists in strengthening the cooperation and coordination of all components of the healthcare system, and especially of all members of the multidisciplinary team, in the management of dyslipidemias, in order to achieve successful therapeutic results.